2021
DOI: 10.3390/brainsci11081087
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of eHealth Adoption in Persons with Multiple Sclerosis and Their Caregivers

Abstract: (1) Background: Persons with multiple sclerosis (pwMS) are often characterized as ideal adopters of new digital healthcare trends, but it is worth thinking about whether and which pwMS will be targeted and served by a particular eHealth service like a patient portal. With our study, we wanted to explore needs and barriers for subgroups of pwMS and their caregivers when interacting with eHealth services in care and daily living. (2) Methods: This study comprises results from two surveys: one collecting data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…The features that PwMS thought they would actually use were symptom logging, performing tests/PROs, treatment overviews and a knowledge center were found to be most popular (84–91%). This is in line with recent research indicating a patient demand for medication schedules and reminders [ 13 ]. This study also indicated a strong interest for visit overviews, which has been implemented into ico mpanion ’s calendar and visit preparation feature recently.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The features that PwMS thought they would actually use were symptom logging, performing tests/PROs, treatment overviews and a knowledge center were found to be most popular (84–91%). This is in line with recent research indicating a patient demand for medication schedules and reminders [ 13 ]. This study also indicated a strong interest for visit overviews, which has been implemented into ico mpanion ’s calendar and visit preparation feature recently.…”
Section: Discussionsupporting
confidence: 91%
“…In order to gain insight into the PwMS' perspective on digital telemonitoring solutions, we carried out a survey which was answered by 45 PwMS of which the larger part (75.2%) indicated to see themselves as digitally literate. Only one patient (2.2%) indicated to have a negative attitude towards using an app to monitor their disease course, which is in line with previous reports about positive attitudes of PwMS [13].…”
Section: Patient Perspectivesupporting
confidence: 90%
See 1 more Smart Citation
“…The main hindering factors that influence the readiness of healthcare professionals in the implementation of an EHR are: sex [50,68], age [50,[69][70][71], knowledge [30,45,50,[72][73][74][75], attitude [74,76,77], awareness [78,79], innovativeness [75], training [63,64,80], computer literacy [50,63,72,74], workload [81], management support [30,82], experience [40,44,46,57,63,64,72,[83][84][85][86], self-efficacy [41,68,87], perceived benefit [30,77,88,89], computer use, and internet access [90].…”
Section: Introductionmentioning
confidence: 99%
“…Haase et al continued their investigation of active stakeholders in the process of digital MS management in a multi-survey study [ 1 ]. They took a close look at the attitudes, needs, and behaviors of pwMS, as well as at their relatives and caregivers regarding electronically assisted disease management.…”
mentioning
confidence: 99%